Journal of Political Economy (Journal of Political Economy, 2017)
Previous articleNext article FreeJournal of Political EconomyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Eliot AbramsDaron AcemogluHunt AllcottTreb AllenRicardo AlonsoGene AmrominGeorge-Marios AngeletosGabriela AntonieKentaro AsaiEnghin AtalayDavid AtkinOrazio AttanasioNed AugenblickPierre AzoulayMatthew BackusMartha BaileyJorge BalatOriana BandieraNicholas BarberisSimcha BarkaiJere BehrmanPeter BellwoodDaniel BenjaminMartin BerajaClaude BerrebiSaurabh BhargavaSaki BigioKen BinmoreChristopher BlattmanMichael BognannoPietro BonaldiAlessandro BonattiStephane BonhommeLex BorghansEthan Bueno de MesquitaMeghan BusseAndrew CaplinPedro CarneiroAmbarish ChandraBriana ChangSylvain ChassangJose CuestaErnesto Dal BoAna De La ODakshina De SilvaFrancesco DecarolisOlivier DeschenesPaul DevereuxCarlos DobkinUlrich DoraszelskiJoseph DoyleOeindrila DubePascaline DupasRuben DuranteChristian DustmannWioletta DziudaBenjamin EdelmanThomas EisenseeArmin FalkHanming FangMaryam FarboodiErnst FehrShuaizhang FengDouglas GaleWilliam GaleManolis GalenianosAlfred GalichonCamilo Garcia-JimenoNicolae GarleanuChristos GenakosSommer GentryMatthew GentzkowUri GneezyDevon GorryGary GortonPiero GottardiLawrence GoulderShane GreensteinMatthew GrennanPaul GriecoJoseph GyourkoGeorge HallWilliam HanlonDavid HemousRichard HornbeckSolomon HsiangJohn Eric HumphriesVictoria IvashinaCharles JonesGreg KaplanAdam KaporMarios KarabarbounisTim KautzBen KeysTerri KneelandDirk KruegerNicolai KuminoffEliana La FerraraSaul LachDavid LagakosKevin LangBrad LarsenJohn LazarevJosh LernerRandall LewisElliot LipnowskiMichael LucaStephen MachinAlexander MackayPaola ManziniFilip MatejkaDavid McKenzieKonrad MenzelMoritz Meyer-ter-VehnGuy MichaelsRobert MoffittEduardo MoralesStephen MorrisMelanie MortenKathleen MullenDavid NeumarkPaul NiehausCarlos NotonMatthew NotowidigdoNathan NunnLee OhanianClaudia OlivettiAmanda PallaisParag PathakDavid PearceCarolin PfluegerThomas PhilipponMaria PolyakovaDevin PopeAndrea PratNancy QianSimon QuinnTarun RamadoraiSergio RebeloStephen ReddingAlbrecht RitschlJames RobertsArthur RobsonJean-Charles RochetNikolai RoussanovRobert RowthornHeather RoyerAldo RustichiniNicholas RyanTobias SalzItay Saporta-EkstenMichael SattingerSusanne SchennachSam Schulhofer-WohlJames SchummerShouyong ShiArtyom ShneyerovMarciano SiniscalchiMichael SinkinsonJagadeesh SivadasanVasiliki SkretaAndrzej SkrzypaczCharles SprengerPhilip StrahanJohannes StroebelJan StuhlerBruno SultanumMatthias SutterAndrew SweetingJustin SydnorChristopher TaberXun TangEmanuele TarantinoHarry ter ReleAlexander TeytelboymMallika ThomasNora TraumMaxim TroshkinNick TsivanidisBertil TungoddenChristopher UdryJohn Van ReenenRichard van WeeldenFrank VerbovenJessica WachterGlen WaddellJohanna WalleniusSimon WeberHeidi WilliamsMatthew WiswallWei XiongNathan YangWilliam ZameTao Zha Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 125, Number 4August 2017 Article DOIhttps://doi.org/10.1086/693975 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.